Promotion of Can Macanan Kaduk Traditional Arts Through Audio Visual Technology - A Lilik Slamet Raharsono; Christanto Pudji Rahardjo (LP2M Universitas Jember, 2019)
Jember Regency is one of the regencies in East Java Province. Here, the growth and development of the culture are extremely rapid and cultural diversity has spread through the southern and northern regions with its respective uniqueness. The southern region is famous for its Javanese culture and the northern region with its Madurese culture. This has led to a combination of the two cultures, resulting in a performing art that is the combination of Javanese and Madurese culture, known as Can Macanan Kaduk. This traditional performing art is an art in Jember that is still maintained by some people. It is needed to support the creation of this performing art and promote it through audio-visual marketing technology so that it will ultimately become widespread and will be better known by the other people outside of Jember. To realize the program objectives, coaching and mentoring has been carried out, regarding the performing arts management with the artists of Can Macanan Kaduk. We create audio-visual work for them to help promote Can Macanan Kaduk. The promotion materials are based on audio-visual technology, consisting of the documentary film, profile videos, and audio-visual advertisement. Through audio-visual promotion and online marketing in websites and offline marketing in DVDs, it is hoped that this traditional performing art, Can Macanan Kaduk, will be widely recognized and gain stronger attention from foreigners, becoming a traditional performing art that characterizes the cultural identity of the Jember Regency. Key Words: Audio Visual Technology, Can Macan Kaduk, Promotion.